2010
DOI: 10.1086/653213
|View full text |Cite
|
Sign up to set email alerts
|

Simian Immunodeficiency Virus–Infected Macaques Treated with Highly Active Antiretroviral Therapy Have Reduced Central Nervous System Viral Replication and Inflammation but Persistence of Viral DNA

Abstract: Background In the era of highly active antiretroviral therapy (HAART) the prevalence of HIV-associated CNS disease has increased despite suppression of plasma viremia. Methods Using an SIV model system where all animals develop AIDS and 90% develop CNS disease by three months postinoculation (p.i.), pigtailed macaques were treated with a regimen of tenofovir disoproxil fumarate, saquinavir, atazanavir, and an integrase inhibitor starting at 12 days and euthanized at ∼175 days p.i. Results Plasma and CSF vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
116
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 104 publications
(124 citation statements)
references
References 51 publications
5
116
3
Order By: Relevance
“…In line with our findings, the persistence of vDNA in the absence of vRNA detection was found in the testis, prostate, and seminal vesicles from juvenile rhesus macaques infected with reverse transcriptase simian-human immunodeficiency virus (SHIV) treated by HAART for 26 weeks (52). A similar differential effect of HAART on vDNA and vRNA levels has been reported in the brain, a well-established HIV/SIV reservoir (67). The lack of HAART impact on vDNA suggests the presence of long-lived cells containing very low vRNA copies, such as latently infected memory T cells (which may be reactivated over time to produce virus and prevent full eradication in the MGT), macrophages producing low level of SIV RNA, or cells harboring defective vDNA.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In line with our findings, the persistence of vDNA in the absence of vRNA detection was found in the testis, prostate, and seminal vesicles from juvenile rhesus macaques infected with reverse transcriptase simian-human immunodeficiency virus (SHIV) treated by HAART for 26 weeks (52). A similar differential effect of HAART on vDNA and vRNA levels has been reported in the brain, a well-established HIV/SIV reservoir (67). The lack of HAART impact on vDNA suggests the presence of long-lived cells containing very low vRNA copies, such as latently infected memory T cells (which may be reactivated over time to produce virus and prevent full eradication in the MGT), macrophages producing low level of SIV RNA, or cells harboring defective vDNA.…”
Section: Discussionsupporting
confidence: 89%
“…The initiation of HAART quickly and drastically decreased viremia. All the treated animals went down to a PVL measurement of Յ100 copies/ml at weeks 3 to 8 after the initiation of HAART (threshold indicative of efficient HAART [52,[65][66][67][68][69], delineated in gray on the graph in Fig. 1B).…”
Section: Resultsmentioning
confidence: 99%
“…With this drug regimen, the number of long-term latently infected resting CD4 ϩ cells in the blood and lymphoid tissues of SIV-infected macaques is comparable to that of HIV-infected patients on HAART, providing an excellent model to study latent HIV/SIV reservoirs, including the CNS. Although viral replication in the brain was dramatically reduced by HAART in this model, viral DNA levels in the brain were unchanged compared to untreated SIV-infected macaques, thus demonstrating that the brain also is a significant viral reservoir (39).…”
Section: Major Histocompatibility Complex (Mhc) Class I-restricted Cd8mentioning
confidence: 75%
“…Our previous studies of the SIV/macaque model have demonstrated that as early as 4 days p.i., a latent reservoir has been established in the brain and the amount of proviral SIV DNA in the CNS reservoir remains stable throughout infection regardless of HAART (1,36,39). However, the presence of the SIV Gag K165R escape mutations in the CNS reservoir suggests that there may be FIG.…”
Section: Discussionmentioning
confidence: 99%
“…Lymphoid and gastrointestinal tissues showed the highest level of viral DNA in virally suppressed animals, suggesting that they consist of the majority of the viral reservoir. In a model of neuropathogenic AIDS, although viremia in plasma and cerebral spinal fluid was significantly reduced by therapy, levels of viral DNA in the brains of these animals were not significantly different than the untreated controls, suggesting that virally infected cells in the central nervous system can contribute to the reservoir (Zink et al, 2010).…”
Section: Evaluating Viral Reservoirs During Antiretroviral Therapymentioning
confidence: 81%